1973
DOI: 10.1107/s0567739473000379
|View full text |Cite
|
Sign up to set email alerts
|

n-Beam lattice images. III. Upper limits of ionicity in W4Nb26O77

Abstract: The scattering factor for electrons is sensitive to differences in atomic bonding at low values of sin 0/2. These differences will influence the amplitudes and phases of low-order beams of electrons diffracted from crystals with large unit cells. The experimental intensities of these beams, and contrast in the corresponding lattice images, can be used to derive upper limits for the charges on constituent ions, provided the associated n-beam dynamical calculations are carried out with sufficient precision. It i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
26
1

Year Published

1975
1975
2013
2013

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(27 citation statements)
references
References 13 publications
0
26
1
Order By: Relevance
“…Individual metal-atom columns became accessible in alloys at 1.8-2.0Å resolution [5], and in silicates at 1.6Å resolution [6]. Development of software for simulation of HREM images from structural models explained the images and confirmed their interpretations [7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Individual metal-atom columns became accessible in alloys at 1.8-2.0Å resolution [5], and in silicates at 1.6Å resolution [6]. Development of software for simulation of HREM images from structural models explained the images and confirmed their interpretations [7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Anstis et al (1973), for example, demonstrated the strong effects that can make lattice image interpretation ambiguous in electron micrographs of a tungsten±niobium oxide. This work has nevertheless been made dif®cult in materials research by the fact that unit-cell sizes in most of the crystals are so small that at the lowest resolution for which data can be recorded, typically 2±5 A Ê , the chemical bonding effect is already very small.…”
Section: Introductionmentioning
confidence: 99%
“…(sin 0)/2 < 0-2 .A,-x, is strongly influenced by the chemical state of the atom, e.g. the valency state (see Anstis, Lynch, Moodie & O'Keefe, 1973). (2) Because of the short wavelength of --~ 100 keV electrons high-order reflections with (sin 0)/2 > 2 A-x, which are the reflections most sensitive to atomic positions, can be observed.…”
Section: Introductionmentioning
confidence: 99%